FutureHome An integrated construction automation approach. - Balaguer, C. (IEEE Robotics and automation magazine)
This article presents the results of the FutureHome project, the first global project in the construction industry that introduces the ICA concept. The design, planning, and onsite robotization stages of house-building construction have been presented. The main advantage introduced by FutureHome is the integration of the three stages under common data and concept. The article focuses on the architectural design of residential houses and office buildings by using prefabricated modules. The design takes into account the prefabrication and onsite assembly. For efficient construction, a global planning strategy has been developed that integrates the prefabrication, transportation, and onsite processes. Finally, the robotized crane for the assembly of big 3-D modules with small tolerances is presented. The control strategy for adequate assembly with the reduction of positioning errors, rotation errors, and swinging of the modules, has been developed and tested